(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
On February 24th 2019, by referendum, the majority of the Cuban population said “yes” to the new Constitution approved on December 22nd 2018 by the delegates of the National Assembly of People’s Power. The new Charter replaced that of 1976, as modified by the reforms of 1992 and 2002. It is not the first time, in fact, that the Cuban ruling class has been able to adapt the constitutional regime of the country to the changes occurred on the international plan and to the new requirements progressively emerged internally. The essay aims to analyze, from a historical perspective, the basic reasons that led the Cuban government to provide the country with a new fundamental Charter, highlighting, at the same time, the most significant innovations introduced.